2006
DOI: 10.1111/j.1525-139x.2006.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology and Dialysis: Management of Lipid Abnormalities Associated with End‐Stage Renal Disease

Abstract: The management of lipid abnormalities in patients with end-stage renal disease (ESRD) remains controversial. Large, well-designed studies investigating the effects of dyslipidemia on cardiovascular (CV) morbidity and mortality and the role of cholesterol lowering drugs in reducing mortality in ESRD patients are lacking. While it seems reasonable to suspect that dyslipidemia and its treatment in ESRD patients will affect CV morbidity and mortality similar to that in the general population, recent studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Several investigations, including the present one, have shown that ESRD patients mainly have more elevated TG and non-HDL-C but not LDL-C (14,28). This may partially explain why the association between fetuin A and dyslipidemia occurs mainly on the non-HDL-C and TG components.…”
Section: Discussionmentioning
confidence: 58%
“…Several investigations, including the present one, have shown that ESRD patients mainly have more elevated TG and non-HDL-C but not LDL-C (14,28). This may partially explain why the association between fetuin A and dyslipidemia occurs mainly on the non-HDL-C and TG components.…”
Section: Discussionmentioning
confidence: 58%
“…22,23 We also found that in the PD group, patients have higher cholesterol and Apo-B levels than in HD group, as reported previously. 7,24,25 A possible explanation for this abnormality is the exposure of patients to glucose in the dialysate and insulin resistance that activates the delivery of free fatty acids (FFAs) to the liver and subsequently the oxidation or esterification of FFAs to cytosolic triglycerides or VLDL. 26,27 The increase of Apo-B concentration in PD patients may possibly enhance the production of Apo-B containing, triglyceride-rich atherogenic particles.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Lipid abnormalities mainly include low levels of highdensity lipoprotein cholesterol (HDL-C), high levels of triglycerides, and elevated levels of triglyceride-rich lipoproteins or lipoprotein remnants. [5][6][7] During oxidative stress, low-density lipoprotein cholesterol (LDL-C) is susceptible to oxidative modification to oxidized LDL (oxLDL). The latter acts as chemoattractant for monocytes and triggers inflammatory reactions within the arterial wall, such as monocyte adhesion to foam cells and monocyte differentiation into macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid abnormalities are common in kidney disease [100,101] and contribute to a high incidence of cardiovascular disorders in this population. Plasma and erythrocyte lipid profiles were examined in CRF patients on hemodialysis for 30 months [102].…”
Section: Effect Of Chronic Kidney Disease and Glomerulonephritismentioning
confidence: 99%